Quantitative risk assessment of wellbore collapse for volcanic rock formation in Sichuan Basin. Issue 2 (October 2021) - Su, Qiang; Guo, Jianhua; Ma, Tianshou; Hu, Xihui
Abstract: Drilling and completion practices for Permian volcanic formation in Sichuan Basin show that the volcanic formation is usually featured by complex lithology, strong heterogeneity, and strong uncertainty. Consequently, a huge risk of borehole collapse is observed during drilling and completion, which seriously affects the safety, efficiency, and costs of natural gas wells. However, the classical analysis method of wellbore stability cannot effectively evaluate the wellbore stability of Permian volcanic formation. Therefore, in view of the complex lithology and strong heterogeneity of volcanic formation, the reliability theory is introduced to conduct the quantitative risk assessment of wellbore collapse for volcanic rock formation. First, the uncertainty analysis model for borehole collapse was introduced based on the reliability theory. Second, the 1D mechanical earth model (MEM) of Permian volcanic formation was proposed by using logging interpretation. Third, the uncertainty of the MEM was assessed by fitting the logging interpretation results. Then, the Monte–Carlo method was used to quantitatively assess the collapse risk of Permian volcanic formation, and the finding was compared with the field testing result. Finally, the sensitivity parameter of borehole collapse was analyzed for Permian volcanic formation. The results indicated that the cohesive strength, internal friction angle, and maximum horizontal stress conformed to a loglogistic distribution; the minimum horizontal stress conformed to an InvGauss distribution, whereas the pore pressure conformed to a Weibull distribution. The equivalent mud weight of critical collapse pressure was approximately 1.88 g/cm 3 when the collapse risk was 5% (i.e., reliability: 95%), which is consistent with the actual situation of the YT-1 well. The sensitivity ranking of wellbore stability parameters were as follows: maximum horizontal in-situ stress > pore pressure > internal friction angle > cohesive strength > minimum horizontal in-situ stress. The present method and results can provide theoretical guidance for the prevention and treatment of wellbore collapse incidents in Permian volcanic formation.